Ekstraksi Tanin dari Limbah Daun Teh pada Berbagai Suhu dan Waktu - Itang Purnama; Jajang Gumilar; Kusmayadi Suradi (CHEMICA: Jurnal Teknik Kimia, 2019)
Green tea leaves old (camellia sinensis) is one of the agricultural waste products that has not been widely used and contains enough high tannin. This study aims to find the tannin content with qualitative and quantitative testing. The design used is a randomized block design with an extraction time of 30 minutes, 40 minutes, and a temperature of 60 °C, 70 °C, and 80 °C treatment repeated 4 times. The results showed that the highest tannin content obtained at the extraction time of 40 minutes at a temperature of 80 °C with a tannin content of 11.55%. The treatment that gave the best results obtained in 40-minute long treatment with a temperature of 70 °C with a tannin content of 10.90%, solubility 29.48% and a pH of 5.80.